Wild Mushroom Identification through Morphological Approaches in middle of West Coast of Peninsular Malaysia - Ling, Sabrina, Shuet Yee; Goh, Yar Yean; Ong, Ghim Hock; Cheng, Wan Hee; Wong, Rui Rui (INTI International University, 2021)
Mushroom has been considered as one of the choices of quality and functional food. Nutritional profiling of mushrooms has been well reported in different research. In Malaysia, most studies investigated secondary metabolite production, cultivation and health benefits of edible mushrooms. Research on wild mushroom has been very limited. Hence, the objective of this research project was to identify the morphology of wild mushroom species commonly found in middle of West Coast of Peninsular Malaysia. Four different wild mushrooms were collected and characterised based on the morphology and growth appearance when cultured on potato dextrose agar. They were morphologically identified as Tremella genus, Ganoderma genus, Phaeolus genus and Trametes genus. However, the species identification was able to confirm up to genus level only as they are sharing many similar features. In conclusion, morphological characterization of mushroom was very time consuming and the accuracy is highly dependent on the researcher’s experience. Therefore, molecular method is needed to further confirm the identity of the wild mushrooms.